A Lighter Shade of Brown? Racial Formation and Gentrification in Latino Los Angeles. (27th November 2019) - Huante, Alfredo
Abstract: Conventional gentrification literature has meaningfully demonstrated how economic inequality is perpetuated in urban settings, but there has been a limited understanding of how racial inequality is maintained. Drawing from participant observation, interviews, and digital ethnography in the barrio of Boyle Heights in Los Angeles that were collected over five years, this study examines how gentrification functions as a racial project and supports new forms of racialization to maintain uneven development along racial lines. Examining the ways that racial formation processes unfurl at the local scale expands conventional understanding of racial formation theory and practice while, simultaneously, illustrating the centrality of place in race-making. This study finds new race and class formations are developed by casting the barrio itself and significant portions of the Mexican American population as "honorary white." Despite colorblind and post-racial ideologies espoused in majority-minority cities like Los Angeles, this landscape fostered emerging racial formations alongside gentrification processes which have increased racial, political, and economic inequality.